A case of transient apical hypertrophy associated with coronary vasospasm. Issue 1 (January 2017) - Awaya, Toru; Moroi, Masao; Takagi, Takahito; Hashimoto, Go; Araki, Tadashi; Hara, Hidehiko; Suzuki, Makoto; Nakamura, Masato; Sugi, Kaoru
Abstract: A 49-year-old woman was admitted to our hospital because of repeated loss of consciousness. On arrival, she was in cardiopulmonary arrest associated with arrhythmia of Torsades de pointes, and recovered from it after cardiopulmonary resuscitation and defibrillation. The administration of a β-blocker and amiodarone was initiated to prevent ventricular tachycardia. On day 2, coronary angiography revealed non-obstructive coronary artery, and left ventriculography (LVG) exhibited hypokinesis in the anterior and apical wall. On day 20, an acetylcholine provocation test revealed a multivessel vasospasm, and LVG showed "spade-shaped left ventricle" in end-diastole because of apical hypertrophy. Transthoracic echocardiography (TTE) also showed apical wall thickness. Subsequent apical wall thickness gradually decreased and returned to normal on day 51 as observed on the TTE. Thus, we report a case of transient apical hypertrophy associated with coronary vasospasm, which was demonstrated by both the TTE and LVG. <Learning objective: A case of transient apical hypertrophy associated with coronary vasospasm was reported with serial left ventriculography and possible mechanisms.>